The Development of Rainbow Spin Learning Media in Social Sciences: ADDIE Development Model - Amiruddin Hasan; Sakdiyah Sakdiyah; Achmad Mustofa; Raudya Tuzzahra (Proceedings of AICS - Social Sciences, 2021)
This paper aims to develop and determine the feasibility of Rainbow spin learning media on interaction material between ASEAN countries at MTs Dayah Modern Arun. This research is a research development or Research Development (RD) with the ADDIE development model. The subjects in this study were students of class VIII MTs Dayah Modern Arun with 31 students plus one social science subject teacher. The instruments used in data collection used validation sheets and questionnaires. The results show (a) Analysis, at this stage the researcher determines the Rainbow spin learning media as a learning medium in overcoming student boredom during the learning process; (b) Design, researchers designed the Rainbow spin learning media design using the Photoshop application before it was made into the original form; (c) Development, Rainbow spin learning media experienced several improvements based on the results of suggestions and validators; (d) Implementation, students look active and enthusiastic in the learning process using Rainbow spin learning media; (e) Evaluation, at this stage it is known that Rainbow spin learning media is suitable for use as learning media. Based on the results of media and material validation, the values obtained were 86.25% and 95% with very feasible criteria. The percentage of teacher responses was 90% with very decent criteria, while the results of student responses got the percentage of 8.33% with very feasible criteria. This means that the Rainbow spin learning media is suitable for use as a learning medium in the material of interaction between ASEAN countries. It is suggested to other researchers that further development or changes need to be made so that the material that can be used in Rainbow spin learning media is not only limited to material interactions between ASEAN countries but also other materials.Keywords: Learning media, Rainbow Spin Game, ADDIE development model